'Horrid Rebellion' and 'Holie Cheate': Royalist Gentry Responses to Interregnum Government In North-East Wales, 1646–1660. (1st June 2018) - Clavier, Sarah Ward
This article significantly adds to works on Interregnum religion and government by considering the response to that period of a conservative, rather than a radical, region and social group. It examines the reaction of the royalist, religiously conservative gentry of north- east Wales to the radical Puritan authorities who governed the region from 1646 onwards. The article argues that the gentry consistently resisted godly government throughout the period 1646–60, destabilizing it by dissent, religious subversion and political action. These measures sustained the 'exiled' Church of England in the 1650s, allowing its clergy and supporters to emerge triumphant at the Restoration.